A Cross-cultural Study of Work Ethic and its Relationship with Locus of Control among the Iranian and Italian Employees - Siroos Ahmadi (جامعه شناسی کاربردی, 2020)
Introduction Work ethic is a fundamentally set of values based on moral virtues of hard work and diligence. Work ethic generally is associated with attendance and punctuality, character (honesty, reliability, self-discipline, self-responsibility), teamwork (respecting the rights of others, being a team worker, being cooperative, being assertive), good appearance, positive attitude and self-confidence, productivity, organizational skills, clear verbal and nonverbal communication, cooperation and good relationships, and respect for oneself and for other people. Work ethic is considered as an important need for every country because human labor with a strong work ethic can play a key role in realizing the national goals. But, many managers and employers believe that it is becoming increasingly difficult to hire workers who have a strong work ethic. Therefore, work ethic and the strategies to improve it have been highly considered. Regarding the cross-cultural studies, Muslim, developing and collectivistic societies have a stronger work ethic than Protestant or Catholic, developed and individualistic cultures. Work ethic obviously influences different aspects of human life, and it is, in turn, affected by micro, meso, and macro factors. While macro level puts emphasis on some wide-ranging causes like economic conditions, cultural values, and religion, meso levels refer to some organizational attributes. And micro levels put more value on individuals and personal attributes like locus of control. There are two indicators to assess work ethic; working hours per week, and national productivity of labor force. Although human labor in Iran with working 44 hours per week is considered as an appropriate work ethic, labor national productivity as another indicator of work ethic is not desirable in this country. The cross-cultural study of work ethic has not received any attention in Iran, and there is no research comparing work ethic between Muslim and Catholics. This research has tried to compare Iran as a Muslim, developing, and collectivistic culture with Italy as a Catholic, developed, and individualistic one. Thus, this research is trying to respond the following questions; 1) is there any significant difference between Iranian and Italian employees in work ethic? 2) Is there any significant relationship between locus of control and work ethic among the Iranian and Italian employees?